PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA SD N DEMAAN DENGAN MENGGUNAKAN PERMAINAN MOKSHAPAT: Penelitian Tindakan Kelas - Faroh Nurunnazlah; Siti Masfuah; Syaffruddin Kuryanto (STKIP Subang, 2024)
This research aims to determine the effectiveness of applying the problem solving learning model to improve the critical thinking skills of grade 4 students at SD N Demaan by using the mokshapat game in mathematics subjects regarding decimal numbers. This classroom action research was carried out in class 4 of SD N Demaan with research subjects of 7 students and 1 teacher which lasted for 2 cycles. Data collection techniques include observation, interviews, documentation and tests. The data analysis used uses qualitative data and quantitative data. The research results in cycle I, critical thinking ability reached classical completeness of 71.4% with an average score of 75. In cycle II, critical thinking ability achieved classical completeness of 85.7% with an average score of 80.7. It has been proven that the application of Problem Solving using the Mokshapat game can improve students' critical thinking abilities and teacher skills in mathematics subjects regarding decimal numbers for grade 4 students at SD N Demaan. Keywords: Critical Thinking Ability, Problem Solving, Mokshapat Game.